2021
DOI: 10.1186/s13071-021-04962-5
|View full text |Cite
|
Sign up to set email alerts
|

High levels of pyrethroid resistance and super-kdr mutations in the populations of tropical bed bug, Cimex hemipterus, in Iran

Abstract: Background The tropical bed bug, Cimex hemipterus, is an important ectoparasite causing various health problems. This species is mainly confined to tropical regions; however, insecticide resistance, global warming, and globalization have changed its distribution map. Molecular information on pyrethroid resistance, which is essential for the development of control programs, is unknown for C. hemipterus in expanded areas. The present study was designed to determine the permethrin resistance statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
(129 reference statements)
0
4
1
Order By: Relevance
“…Cimex hemipterus was reported from northwestern and the west of Iran based on unmentioned morphological criteria and molecular studies (11). Some reports from other regions of the country indicate the presence of C. hemipterus (12,18). Cimex lectularius was reported from Mashhad in 2019 (19), and in the present study, we could not find this species in the study area, including Mashhad city.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Cimex hemipterus was reported from northwestern and the west of Iran based on unmentioned morphological criteria and molecular studies (11). Some reports from other regions of the country indicate the presence of C. hemipterus (12,18). Cimex lectularius was reported from Mashhad in 2019 (19), and in the present study, we could not find this species in the study area, including Mashhad city.…”
Section: Discussioncontrasting
confidence: 70%
“…The identification of bed bugs at the species level is usually based on morphological characteristics such as pronotum, hind tibial, paragenital sinus, and paramer (12). The pronotum width-to-length ratio is the most influential factor for differentiating C. hemipterus and C. lectularius.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects were significantly higher compared to either deltamethrin or propetamphos agents . Cimex lectularius used to be widespread in Iran, but now it has been replaced by C. hemipterus as the predominant species ( 11 ). In our previous study, we showed that diazinon, λ-cyhalothrin, and malathion were not effective against C. lectularius populations in northeastern Iran ( 12 ), however, this study demonstrated that bed bugs are susceptible to phoxim.…”
Section: Discussionmentioning
confidence: 99%
“…In C. lectularius , 3 kdr mutations (V419L, L925I, and I936F) have been reported (Yoon et al 2008, Zhu et al 2010, Dang et al 2015a), whereas 9 kdr mutations (L899V, M918I, D953G, L1014F, Y/L995H, V1010L, I1011F, V1016E, and L1017F/S) have been reported in C. hemipterus (Dang et al 2015b, Punchihewa et al 2019). In particular, the double mutation of M918I and L1014F is known as a super-knockdown resistance ( super-kdr ) mutation (Ghavami et al 2021). In addition, the F348Y mutation associated with resistance to organophosphates and carbamates in the paralogous acetylcholinesterase gene ( p-Ace ) was recently identified in both bed bug species (Komagata et al 2021).…”
Section: Introductionmentioning
confidence: 99%